Technical Guidance on The Integration of Cattle and Food Crops in Sindang Kasih Village, South Konawe District - Hafid, Harapin; Ananda, Siti Hadrayanti; Dedu, La Ode Arfan; M. Aslan, La Ode; Tasse, Andi Murlina; Pancar, Fadli Ma'mun (Journal of Saintech Transfer, 2024)
This technical guidance aims to provide understanding to cattle breeders regarding the benefits of integrating cattle and food crops in one area so that participants are motivated and encouraged to carry out integration between cattle and food crops. This technical guidance was implemented at Sindang Kasih Village, West Ranomeeto District. Implementation of technical guidance uses lecture and discussion methods. The tools and materials used are vehicles, cell phones, and laptops. In general, Cattle Farmers in Sindang Kasih Village already understand the integration of cattle and food crops and its benefits and are committed to implementing this integration as indicated by the ability of all participants to answer questions correctly at the end of the activity session (100%). The challenges and problems of beef cattle farming include maintenance and waste processing systems. Integrating livestock with food crops in Sindang Kasih Village has been implemented well. The livestock in Sindang Kasih needs to be further improved to become one of the breeding and fattening centers in Southeast Sulawesi.